2014
DOI: 10.1080/10826076.2012.749501
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON A SIMPLE AND EFFICIENT METHOD FOR LARGE-SCALE PREPARATION OF GENKWANIN FROM DAPHNE GENKWA SIEB. ET ZUCC. USING NORMAL-PHASE FLASH CHROMATOGRAPHY

Abstract: Genkwanin, a flavonoid which has anti-oxidant and anti-tumor activities, was isolated and purified from flowers of Daphne genkwa Sieb. et Zucc. in a large-scale by normal-phase flash chromatography (NPFC). Dried flower buds were extracted with methanol at room temperature and concentrated. The residues were suspended in water and first extracted with petroleum ether, and then chloroform. Genkwanin was concentrated in the chloroform and insoluble fractions. Under the target-guidance of thin layer chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…All of the tentatively identified compounds and their content on dry rosemary basis, obtained with the different solvent’s concentrations, after 70 min of extraction, are presented in Table 3 . The respective mean retention times (r.t.) of the standard compounds, as reported in literature [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and also found in the present work, are also presented.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…All of the tentatively identified compounds and their content on dry rosemary basis, obtained with the different solvent’s concentrations, after 70 min of extraction, are presented in Table 3 . The respective mean retention times (r.t.) of the standard compounds, as reported in literature [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and also found in the present work, are also presented.…”
Section: Resultssupporting
confidence: 86%
“…Apigenin presents r.t. = 48.6 min, and spectral maxima at 268 and 338 nm, while 4′-methyl-apigenin (acacetin) elutes at 50.5 min (λ max = 268, 334 nm, apigenin-type spectrum). Genkwanin is another mono-methylated apigenin derivative, detected in rosemary [ 31 , 33 , 34 , 40 , 46 ] with average maxima, according to the above references at 268 and 338 nm, equal to those of peak c ( Supplementary Figure S1 ). In agreement with previous analysis of Artemisia extracts that contained the mono-methylated apigenin derivatives, acacetin and genkwanin [ 47 ], the higher retention time of peak c (50.8 min) also indicated genkwanin.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, genkwanine was the compound eluted at 42.37 min with deprotonated [M‐H] − at m / z 283.06201 in agreement with the literature data (Borrás Linares et al, ). This flavonoid was found in rosemary leaves (Borrás‐Linares et al, ), in the seeds of Alnus glutinosa (O'Rourke et al, ) and in the flowers of Daphne genkwa , and it is well known for its antioxidant and anti‐tumour activities (Shu et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…Prior chemical studies have shown that Genkwa flos encompasses various types of constituents involving flavonoids, diterpenoids, lignans, and coumarins [ 100 ]. Current emerging evidence indicates that severe lesions to cardiac, renal, hepatic, and cutaneous tissues can be identified by excessive and prolonged administration of Genkwa flos [ 101 , 102 , 103 , 104 ]. Hepatotoxicity of Genkwa flos treatment have shown in HL-7702 liver cells, such as the increased hepatic serum makers of ALT, AST, and MDA, and downregulated oxidative stress indexes of CAT and GSH.…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%